A cytomegalovirus inflammasome inhibitor reduces proinflammatory cytokine release and pyroptosis - Y. Deng; Eléonore Ostermann; Wolfram Brune (2024)
Abstract In response to viral infection, cells can initiate programmed cell death (PCD), leading to a reduction in the release of viral progeny. Viruses have therefore evolved specific mechanisms to curb PCD. Cytomegaloviruses (CMVs) are sophisticated manipulators of cellular defenses and encode potent inhibitors of apoptosis and necroptosis. However, a CMV inhibitor of pyroptosis has not been clearly identified and characterized. Here we identify the mouse cytomegalovirus M84 protein as an inhibitor of pyroptosis and proinflammatory cytokine release. M84 interacts with the pyrin domain of AIM2 and ASC to inhibit inflammasome assembly. It thereby prevents Caspase-1-mediated activation of interleukin 1β (IL-1β), IL-18, and Gasdermin D. Growth attenuation of an M84-deficient MCMV in macrophages is rescued by knockout of either Aim2 or Asc or by treatment with a Caspase-1 inhibitor, and its attenuation in infected mice is partially rescued in Asc knockout mice. Thus, viral inhibition of the inflammasome-pyroptosis pathway is important to promote viral replication in vivo.